Information transmission between banks and the market for corporate control - Christian Bittner; Falko Fecht; Melissa Pala; Farzad Saidi (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
This paper provides evidence of deliberate private-information disclosure within banks' international business networks. Using supervisory trade-level data, we show that banks with closer ties to a target advisor in a takeover buy more stocks of the target ffrm prior to the deal announcement, enabling them to benefft from the positive announcement return. We do not ffnd such effects for bank connections to acquirer advisors or for trades in acquirer stocks. Target advisors benefit from leaking information about takeover bids to connected banks, as it drives up the premium paid without compromising the probability of bid success.
Keywords: G11; G15; G21; G24; 330; bank networks; trading; information spillovers; mergers and acquisitions; syndicated lending